Lactate and lactylation in sepsis-associated acute kidney injury: clinical evidence from the MIMIC-IV database and mechanistic insights - Zhang, Sujing; Luo, Mengyuan; Lu, Zhijie; Shi, Qiqing (Frontiers in Medicine, 2025)
BackgroundSepsis-associated acute kidney injury (SA-AKI) is a common and severe complication of sepsis, yet early predictors remain limited. Lactate, beyond being a marker of tissue hypoperfusion, may act as a signaling molecule through protein lactylation. This study aimed to investigate the association between lactate levels and SA-AKI risk using the MIMIC-IV database and to explore the potential mechanistic role of lactylation in septic mice.MethodsAdult sepsis patients were identified from the MIMIC-IV (v3.1) database. Patients were stratified by lactate tertiles within 24 h of ICU admission, and lactate clearance (LC) was assessed as a dynamic indicator. The primary outcome was SA-AKI, and secondary outcomes included CRRT use and 28-day mortality. Kaplan–Meier analysis, Cox regression, and restricted cubic spline (RCS) models were performed. In parallel, a murine cecal ligation and puncture (CLP) model was used to evaluate tissue-specific protein lactylation by Western blot, along with serum lactate and hematological parameters.ResultsA total of 11,431 patients were included. Higher lactate levels were associated with increased disease severity, higher incidence and severity of SA-AKI, greater use of CRRT, and elevated 28-day ICU and in-hospital mortality. In Cox regression, lactate as both a continuous and categorical variable was independently associated with SA-AKI risk. RCS analysis revealed nonlinear dose–response relationships, with sharply increased risk of SA-AKI above 5.7 mmol/L. In sensitivity analyses (n = 6,593), higher LC was associated with lower risks of SA-AKI, CRRT use, and mortality. Cox regression confirmed LC as an independent protective factor, while RCS suggested a downward but non-significant trend. In the CLP mouse model, protein lactylation was markedly elevated in the kidney but not in the heart, liver, or spleen, accompanied by higher serum lactate.ConclusionElevated lactate levels are independently associated with increased risk of SA-AKI in sepsis patients, whereas higher lactate clearance is linked to improved renal outcomes. Moreover, kidney-specific upregulation of protein lactylation in septic mice suggests a possible molecular link between lactate metabolism and renal vulnerability. These findings highlight lactate and lactylation as both prognostic markers and potential mechanistic contributors in SA-AKI.